Evaluasi Pengakuan, Pengukuran, Pengungkapan Terhadap Pendapatan Kontrak Pelanggan Menurut PSAK No. 72 di PT Guna Bangun Wisata Tahun 2021-2022 - Yolanda Mayusfa (Jurnal Akuntansi Nommensen, 2023)
In the implementation of PSAK No. 72 replaces PSAK No. 23 which is PSAK No. 72 will adopt a more complete version of IFRS 15 Revenue From Contracts With Customers. PSAK No. 72 will be a single standard for revenue recognition that applies to most contracts with customers, replacing the existing accounting guidance under SAK contained in various standards. This research will be conducted at PT Guna Bangun Wisata which is a company operating in the real estate sector. The type of research used is descriptive qualitative. The company's main source of income is rental income and service charges for both standard tenants and premium tenants. The results of this research state that for the recognition and disclosure of income in the company PT In order to develop tourism without being able to implement PSAK No. 72 because PT Guna Bangun Wisata recognizes income proportionally when the tenant has signed a rental contract. However, income measurement is fully in accordance with PSAK No.72. PT Guna Bangun Wisata only measures part of the contract information with customers. Meanwhile, the presentation in PSAK No. 72 states that if the customer pays compensation, or the company has the right to the amount of unconditional compensation (receivables), before the company transfers the mutually agreed contract to the customer.